Production of Biofuel (Bio-Ethanol) from fruitwaste : Banana Peels: article - Ahmad, Nor Elina; Alias, Azil Bahari (2019)
Bioethanol are known as the renewable energy and an economically friendly type of energy where it can replaced the uses of natural gas and also petroleum in the future. Banana peels are classified in fruit waste category where it can be used as the raw material in producing ethanol since it have high content of cellulose and low content of lignin. This study has conducted in order to observe the concentration of ethanol produce from the banana peels through few steps which were pretreatment, hydrolysis and also fermentation process. This study were focusing on the effect of pH value on the concentration ethanol from banana peels. Different pH value has been applied in the hydrolysis process where it is in the range of 4 to 12 in order to observe the optimum pH value in producing ethanol